A força do riso como máquina de luta entre a atenção e o apego à vida: cartografias das aprendências em uma escola pública - Lourenco, Suzany Goulart (2019)
This research aims to cartography traces that the laugh shows to the possibilities of attention to life and attachment to life in the curricula movements. Movements these that unfold themselves in learnincy among teachers and students in a public school. It indicates that the attention to life relate itself to a certain type of answer to the social requirement and that the attachment to life moves the thought beyond the intelligence, boosting – from the creating emotion – the movements and not only the shape. It defends the thesis that the strength of laughing intertwine with the learning process’ in the school’s composition plane, constituting ways of attention and attachment to life that displace the thought and potentialize the invention and the creating emotion. It uses mainly the proposition of Henri Bergson, Gilles Deleuze and Félix Guattari. Highlights the current political scenery as catastrophic in which generate serious micropolitical effects, since it propagates the insecurity and the fear of the collapse. It observes that, in this scenery, the laugh isn’t desirable, once it is expected that the automatism reigns and become accepted without delay. The more automatically it suits the commanding words, more pleasured will be the ones that feed on passivity. The study problematizes subjectivation process’ that subverts the Capitalistic times and laugh at the idea that all images are already taken beforehand, since the subjectivation process suffers subjection, but also resists. It wagers on laughing as a fight machine, as an assembling gesture of communistic curricular movements that opposes themselves to the Capitalistic reign, boosting an inventive effort. It cartographes the learnincy invented in the Horizon School, a primary school located in the city of Serra/ES, specifically in the neighborhood of New Horizon, using con-verse-action, observations, images and intervention to produce the cartography. It understands the cartography as a witchcraft because it is produced as a research of alliance and contagion, enabling make see different lines that crosses the subjectivation process, the block of intensity and the becoming. It also thinks the laughing and its potentialities to make visible the dreams of school of teachers and students, moving against the absolute certain and enabling to glimpse variations and displacing inherited habits. It concludes betting on the strength of the public school to conspire other possible worlds from the communistic weaving of curricula that enable the laugh to dance among faces, bringing to the surface, as in Don Quixote, the windmill, disturbing our sensorimotor schema and constituting infinite becomings.